The Impact of Bank Credit on the Gross Domestic Product in Iraq - Waleed Ashour Khaleed (European Science Publishing, 2024)
In the Vision 2030, which aims to increase the productivity of the Iraq economic sectors, the importance of measuring the outputs of the use of economic resources by those sectors emerges, as well as the importance of identifying the factors affecting the increase in the output of each of those sectors. From here, the current study began to measure the impact of bank credit granted by Iraq banks on the gross domestic product. The study also aimed to measure the impact of bank credit on the contribution of the economic sectors operating in Iraq to the gross domestic product. Detailed data on bank credit were used according to the economic sectors benefiting from it, and detailed data on the contribution of these sectors to the GDP. A regression analysis was conducted for time series representing bank credit and representing the contributions of economic sectors to the Iraq GDP, and it was found that there was a partial effect of bank credit on the contributions of Iraqi economic sectors to the Iraqi GDP. The different economic sectors particularly affect the contributions of the energy and basic utilities sectors, and this indicates that the financing granted to the economic sectors is often used for operational purposes. This raises a question mark about the efficiency of those sectors in terms of their benefit from bank credit in expansion and growth and in increasing their contributions to the Iraqi GDP. Economic sectors for the financing granted to them.
Keywords: bank credit, economic sectors, gross domestic product.